INDUCTIVE AND DEDUCTIVE TEACHING METHODS: THEORETICAL FOUNDATIONS, COGNITIVE MECHANISMS, AND PEDAGOGICAL IMPLICATIONS - Ashurova Madina Isroilovna (Innovate Conferences, 2025)
This article examines the inductive and deductive teaching methods as two fundamental epistemological approaches in contemporary didactics. Their theoretical underpinnings, cognitive mechanisms, and practical implications for instruction are analyzed through a comprehensive academic lens. The discussion highlights how the inductive method facilitates concept formation through empirical observation and generalization, whereas the deductive method structures learning around pre-established theoretical principles applied to specific cases. The paper argues that the pedagogical effectiveness of both methods depends not merely on their mechanical use but on their alignment with the logic of the subject matter, the intended learning outcomes, and learners’ cognitive development. A comparative analysis and integration framework are also provided, demonstrating how the systematic combination of both approaches strengthens students’ analytical abilities, conceptual understanding, and transferable competencies.
Keywords: inductive method, deductive method, didactics, cognitive development, conceptual generalization, instructional logic, epistemology of learning.